IDNLearn.com provides a comprehensive solution for all your question and answer needs. Discover the information you need quickly and easily with our reliable and thorough Q&A platform.
Sagot :
To solve the equation [tex]\( 10(x-1) = 8x - 2 \)[/tex] for [tex]\( x \)[/tex], follow these steps:
1. Distribute the 10 on the left-hand side:
[tex]\[ 10(x - 1) = 10x - 10 \][/tex]
So the equation becomes:
[tex]\[ 10x - 10 = 8x - 2 \][/tex]
2. Combine like terms involving [tex]\( x \)[/tex]:
Subtract [tex]\( 8x \)[/tex] from both sides to get all [tex]\( x \)[/tex]-terms on one side:
[tex]\[ 10x - 8x - 10 = -2 \][/tex]
Simplifying this, we get:
[tex]\[ 2x - 10 = -2 \][/tex]
3. Isolate the [tex]\( x \)[/tex]-term:
Add 10 to both sides to get rid of the constant term on the left side:
[tex]\[ 2x - 10 + 10 = -2 + 10 \][/tex]
Simplifying this, we have:
[tex]\[ 2x = 8 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{2x}{2} = \frac{8}{2} \][/tex]
Simplifying this, we get:
[tex]\[ x = 4 \][/tex]
So, the value of [tex]\( x \)[/tex] that solves the equation [tex]\( 10(x-1) = 8x - 2 \)[/tex] is [tex]\( x = 4 \)[/tex].
Therefore, the correct answer is [tex]\( x = 4 \)[/tex].
1. Distribute the 10 on the left-hand side:
[tex]\[ 10(x - 1) = 10x - 10 \][/tex]
So the equation becomes:
[tex]\[ 10x - 10 = 8x - 2 \][/tex]
2. Combine like terms involving [tex]\( x \)[/tex]:
Subtract [tex]\( 8x \)[/tex] from both sides to get all [tex]\( x \)[/tex]-terms on one side:
[tex]\[ 10x - 8x - 10 = -2 \][/tex]
Simplifying this, we get:
[tex]\[ 2x - 10 = -2 \][/tex]
3. Isolate the [tex]\( x \)[/tex]-term:
Add 10 to both sides to get rid of the constant term on the left side:
[tex]\[ 2x - 10 + 10 = -2 + 10 \][/tex]
Simplifying this, we have:
[tex]\[ 2x = 8 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{2x}{2} = \frac{8}{2} \][/tex]
Simplifying this, we get:
[tex]\[ x = 4 \][/tex]
So, the value of [tex]\( x \)[/tex] that solves the equation [tex]\( 10(x-1) = 8x - 2 \)[/tex] is [tex]\( x = 4 \)[/tex].
Therefore, the correct answer is [tex]\( x = 4 \)[/tex].
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.